A Systematic Review of Integrated Learning Definitions, Frameworks, and Practices in Recent Health Professions Education Literature - Davina Matinho; Marisa Pietrandrea; Carlos Echeverria; Ron Helderman; Madison Masters; Daniel Regan; Samuel Shu; Rafael Moreno; Douglas McHugh (MDPI AG, 2022)
International curricular redevelopment and quality improvement efforts include integration within and across disciplines as a focal point. Definitions and applications of the term 'integration' vary routinely in health professions education literature, weakening opportunities to enhance our educational practice through collaborative, interprofessional knowledge-sharing. This systematic review examined recent health professions education literature for reported definitions, theories or frameworks, and educational activities around integrated learning, education, curricula, or teaching. A total of 35 articles representing learners from 12 different health professions, between 2017 and 2021, were analyzed through a literature search of seven databases: PubMed, Scopus, CINAHL, JSTOR, the Cochrane Library, LGBTQ + Life, and ERIC. Full-text retrieval and data extraction of the included studies were conducted. Of the 35 articles reviewed, 13 included explicit definitions of integration (an additional six alluded to a definition), 19 referred to an educational theory or framework used to guide integration design efforts, and 27 mentioned teaching methods by which integration was implemented. Misunderstanding what is meant by integrated, how others have planned for it, or how others have sought to bring it about practically, all threaten attempts to improve the cultivation of health professionals as integrated thinkers and holistic care providers.